Operation features of the pulse penning ion source in the transition pressure range. (November 2019) - Mamedov, N V; Maslennilov, S P; Solodovnikov, A A; Yurkov, D I
Abstract: The paper presents the results of experiments studying the dependence of discharge and extracted currents on the pressure of pulsed penning ion source (PIS). A comparative analysis of the amplitude-time and current-voltage characteristics of PIS for the various anode voltage amplitudes, pulse repetition rates, pulse durations, magnitudes (and configurations) of the magnetic field is presented. The obtained results reveal the existence of different (stable and unstable) discharge modes depending on the operating conditions of the power supply system and the pressure range of the working gas (deuterium). The features of current waveforms in the transitional pressure range 0.5–2 mTorr are defined.